The effects of Voluntary Disclosure Program (VDP) and tax sanctions on individual taxpayer compliance - Sang Made Sandwi Putra; Wayan Hesadijaya Utthavi; Ketut Nurhayati (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Tax revenue has an important role in national development. The government continues to pursue various policies to improve taxpay-er compliance so that tax revenues can increase. One of the efforts made by the government is to pass the Law on the Harmonization of Tax Regulations. One of the programs contained in the law is the voluntary disclosure program (VDP). The purpose of this research is to find out the effect of the Voluntary Disclosure Program (VDP) and Tax Sanctions on Individual Taxpayer Compliance. The type of research applied in this study is quantitative research with a correlational approach. In this study, the population studied were individual taxpayers registered at KPP Pratama Badung Selatan, using purposive sampling techniques in sampling based on predetermined criteria and using the slovin formula, so as to get a sample of 100 respondents. The data used in this study was primary data using a likert scale of scores 1 to 4. The data analysis technique used in this study is multiple linear regression using the SPSS v.26.00 software program. The results of this research show that the voluntary disclosure program has a significant positive effect on taxpayer compliance, tax sanctions have a significant positive effect on taxpayer compliance, and the voluntary disclosure program and tax sanctions simultaneously have a significant effect on Taxpayers compliance.